2022
DOI: 10.1039/d2lc00737a
|View full text |Cite
|
Sign up to set email alerts
|

Surface acoustic wave microfluidics for repetitive and reversible temporary immobilization of C. elegans

Abstract: Caenorhabditis elegans is an important genetic model for neuroscience studies, used for analyses of how genes control connectivity, neuronal function, and behavior. To date, however, most studies of neuronal function...

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 56 publications
(75 reference statements)
0
4
0
Order By: Relevance
“…By adjusting the duration and power intensity of SAW actuation, an optimal exposure setting has been found that substantially mitigates neurodegenerations in both models. This research underscores the nuanced relationship between exercise parameters and neuroprotection in C. elegans, unveiling the acoustofluidic gym as an instrumental tool for further inquiries in this domain [141,142]. More clinically, Gai et al have contributed an innovative, automated methodology for the selection of high-quality sperm, targeting the resolution of male infertility [143,144].…”
Section: Acoustofluidic Biophysical Therapymentioning
confidence: 86%
“…By adjusting the duration and power intensity of SAW actuation, an optimal exposure setting has been found that substantially mitigates neurodegenerations in both models. This research underscores the nuanced relationship between exercise parameters and neuroprotection in C. elegans, unveiling the acoustofluidic gym as an instrumental tool for further inquiries in this domain [141,142]. More clinically, Gai et al have contributed an innovative, automated methodology for the selection of high-quality sperm, targeting the resolution of male infertility [143,144].…”
Section: Acoustofluidic Biophysical Therapymentioning
confidence: 86%
“…Although conventional techniques, such as the use of nanoparticles [35] and hydrogel encapsulation [36], work reasonably well in worm immobilization, they still require time-consuming manual operations. In contrast, microfluidic technology provides new possibilities for immobilization by restricting the movement of C. elegans and inhibiting its physiological activities [75][76][77][78][79][80][81][82][83][84][85][86][87][88][89][90]. The automated nature of microfluidic platforms eliminates the need for manual processing, saving time and resources [73,74].…”
Section: Microfluidic Approaches For Immobilizationmentioning
confidence: 99%
“…However, further research is needed to assess the potential impact of this method on the worms' physiology. Similarly, Sridhar et al discovered that surface acoustic waves (SAW) could be used to immobilize worms [90]. This non-contact method enables quick immobilization by exerting SAW acoustic force on the worms through interdigitated electrodes on piezoelectric materials.…”
Section: Microfluidic Approaches For Immobilizationmentioning
confidence: 99%
“…27 To date, SAW-based miniaturized devices have been widely used in the manipulation and characterization of biological objects. 5,16,18,[28][29][30][31][32][33][34][35][36][37] The SAW technology has also been an emerging and powerful tool in biomedical fields such as bioanalysis and chemical research. 38 SAW-based microfluidics allows a direct manipulation of liquids and particles suspended in liquids in a strong-gradient acoustic field.…”
Section: Introductionmentioning
confidence: 99%